Prevalence of right ventricular perfusion defects after inferior myocardial infarction assessed by low-level exercise with technetium 99m sestamibi tomographic myocardial imaging - Travin, Mark I.; Malkin, Robert D.; Garber, Carol Ewing; Messinger, Debra E.; Cloutier, Donna J.; Heller, Gary V. (The American heart journal, 1994)
To assess the prevalence of right ventricular perfusion defects after a recent inferior wall myocardial infarction, 33 patients were studied 6 to 14 days after infarction with low-level exercise testing and technetium 99m ( 99mTc) sestamibi (SPECT) imaging. Twenty-two control subjects with a <5% likelihood of coronary artery disease undergoing exercise 99mTc sestamibi imaging were also studied. For each image the right ventricle was computer isolated from reconstructed transverse cardiac slices, followed by reorientation into oblique slices. Both right and left ventricular images were visually assessed for defects. A quantitative method of defect detection was also applied to the right ventricle. For the right ventricle, 100% of the stress images and 96% of the rest images were adequate for interpretation. Right ventricular stress perfusion defects were identified in 10 (30%) of 33 patients with recent inferior infarction, with 50% completely or partially normalizing on rest images, consistent with ischemia. Of 14 patients with left ventricular inferoseptal defects, eitht (57%) had right ventricular defects compared with 2 (11%) of 19 without inferoseptal defects ( p < 0.005). We concluded that the right ventricle can be adequately assessed for perfusion defects by means of exercise with 99mTc sestamibi SPECT imaging. Defects of the right ventricle after inferior myocardial infarction occur frequently, and many have evidence of ischemia. Right ventricular perfusion defects are closely associated with left ventricular inferoseptal defects.